Strengthening effect of crushed rock revetment and thermosyphons in a traditional embankment in permafrost regions under warming climate - Qi-Hang Mei; Ji Chen; Jin-Chang Wang; Xin Hou; Jing-Yi Zhao; Shou-Hong Zhang; Hai-Ming Dang; Jia-Wei Gao (Advances in Climate Change Research, 2021)
The embankment of the Qinghai–Tibet Railway (QTR) has been experiencing severe problems due to permafrost degradation, especially in warm and ice-rich permafrost regions. Based on ground temperature and deformation data of the embankment at location K1497 + 150 of the QTR in 2006–2018, the thermal regime and deformation process were analysed. The results showed that 1) the degradation rate of permafrost under the embankment was faster than that under the natural site without engineering construction, and 2) the deformation rate of the embankment had exceeded the safety range for the QTR embankment before adopting mitigative measures. In addition, this study evaluated the cooling effect on the underlying permafrost and working mechanism of two strengthening measures. Two measures, crushed rock revetment (CRR) and thermosyphons, were adopted to protect the underlying permafrost from continual degradation. The individual cooling effect of the CRR was not as good as that of the thermosyphons. However, the combination of the two could enhance the protective effects of each on the underlying permafrost, effectively cooling the permafrost and improving the stability of the embankment.